Study Status and Developing Trend of Electric Cylinder - Chen Chao; Zhao Shengdun; Cui Minchao; Cai Houyong; Li Xue (Jixie chuandong)
The characteristics and performance requirements of electric cylinder are described,and some of the electric cylinder application are listed.The research status of electric cylinder at home and abroad are introduced,and the common structure of electric cylinder at present is expound.Finally,the development trend of electric cylinder is discussed.